STRATEGI PENGAMBILAN KEPUTUSAN DALAM DINAMIKA KEPEMIMPINAN PUNCAK IMPLIKASINYA TERHADAP KINERJA PERUSAHAAN PERBANKAN DI INDONESIA - Feby Widia Putri; Nurma Dewi Mufaati; Rani Haerani; Bintang Alya Binurika Mustopa; Hadi Supratikta (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to examine the dynamics of leadership within the Top Management Team (TMT) and their influence on strategic decision-making processes in Indonesian banking institutions. Using a descriptive qualitative approach, data were collected through document analysis and indirect interviews with TMT members. The findings indicate that diversity within TMTs particularly in terms of educational background, professional experience, and gender positively contributes to the quality and innovativeness of strategic decisions. Such diversity enables teams to formulate more creative and adaptive strategies in response to external shifts, including advancements in digital technologies and changes in banking regulations. Nevertheless, the study also reveals challenges related to achieving consensus among team members, which may impede decision making efficiency if not effectively managed. In addition, the distribution of power within TMTs whether centralized or dispersed significantly shapes the dynamics and effectiveness of strategic decision-making. Overall, the results underscore the importance of managing diversity and fostering collaborative leadership within TMTs to enhance the strategic capabilities of banks operating in an increasingly dynamic and competitive industry landscape.